Expression of TLE1 in Malignant Melanoma With Spindle Cell Morphology: A Potential Diagnostic Pitfall. (May 2019) - Morrell, Travis J.; Xiong, Yiqin; Deng, April; Dresser, Karen; O'Donnell, Patrick; Cornejo, Kristine M.
Objectives . Transducer-like enhancer of split 1 (TLE1) immunohistochemistry is widely used as a biomarker of synovial sarcoma. Spindle cell or desmoplastic melanoma can morphologically mimic synovial sarcoma. The aim of this study was to investigate the expression of TLE1 in melanomas with a spindle cell morphology. Methods . A search of the surgical pathology files resulted in 57 cases of melanomas diagnosed with a spindle cell or desmoplastic component. After review, 8 cases had no definitive dermal spindle cell component and 7 cases had insufficient tissue remaining and were excluded from the study. A total of 42 melanomas were examined for TLE1 immunohistochemistry using a mouse monoclonal antibody (Cell Marque, clone 1F5). Strength and percentage of nuclear TLE1 positivity was graded on a scale from 0 to 3+. Staining for TLE1 was considered positive for 2 to 3+ and negative for 0 to 1+. Results . Nuclear TLE1 expression was identified in 24 (57%) of the 42 melanoma cases with spindle cell morphology (2+, n = 14; 3+, n = 10). TLE1 was considered negative in 18 cases (43%), of which most contained weak staining (1+, n = 14 [33%]) and only a small subset did not show any staining (0, n = 4 [10%]). Conclusion . TLE1 frequently highlights melanomas with spindle cell morphology and is a potential diagnostic pitfall. Therefore, when evaluating spindle cell tumors in which the differential may include both a melanoma and synovial sarcoma, TLE1 expression should be interpreted with caution and in conjunction with an immunohistochemical panel.